1995
DOI: 10.1364/josab.12.002398
|View full text |Cite
|
Sign up to set email alerts
|

Čerenkov-type second-harmonic generation in thin planar calix[4]arene waveguiding films

Abstract: A new type of organic molecule, calix[4]arene, is applied in a second-harmonic-generating waveguide device for the first time. Linear optical properties of the calix[4]arene waveguiding film have been measured with the prism-coupling method. The molecules in the film are oriented by a corona-poling technique. With a Makerfringe experiment, the induced d 33 and d 31 at l 1064 nm are determined at 8.6 and 2.0 pm͞V, respectively. The calix[4]arene thin film has been applied to aČerenkov-type device that generates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The films were allowed to cool to room temperature while the voltage was maintained. The orientation parameter cos 3 θ of the films was calculated as described in ref and varied between 0.2 and 0.3. The SHG efficiencies of the films were measured with a Q-switched Nd:YAG laser at 1064 nm fundamental wavelength, using α-quartz as a reference ( d 11 = 0.51 pm V -1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The films were allowed to cool to room temperature while the voltage was maintained. The orientation parameter cos 3 θ of the films was calculated as described in ref and varied between 0.2 and 0.3. The SHG efficiencies of the films were measured with a Q-switched Nd:YAG laser at 1064 nm fundamental wavelength, using α-quartz as a reference ( d 11 = 0.51 pm V -1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Noordman et al have shown that with neat films of (tetranitrotetrapropoxy)calix[4]arene frequency doubling from 820 to 410 nm is possible with efficiencies up to 0.23% over a path length of 6 mm in a Cerenkov-type device 13a. Efficiencies of that order of magnitude and higher (2 orders of magnitude is feasible 13a ) should also be obtainable with the polymer films 7a and 7b since the absorption properties of these films are, as expected, similar to or even better than the neat calix[4]arene films used in the Cerenkov-type devices.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The sample was rotated, and the SHG measurement was conducted in both the s f p and p f p polarized geometry. Therefore, assuming that the Kleinman symmetry rule was valid, 14 we used the s f p fringe to calculate the d 31 (d 31 = d 15 ) and the p f p fringe to calculate the d 33 value. The SHG signal was normalized with respect to that of a calibrated quartz crystal wafer (X-cut) 1 mm thick whose d 11 is 0.46 pm/V.…”
Section: ' Introductionmentioning
confidence: 99%
“…Functionalized calix[4]arene molecules have been applied in various areas including sensors, molecular recognition, and molecular switches ), combining four donor−π-acceptor chromophoric units in one molecule, has interesting nonlinear optical properties. In this paper we report on our studies of the material properties of neat 1 in the solid phase and in thin films. The typical phase transition of solid 1 at temperatures between 130 and 140 °C was investigated in detail.…”
Section: Introductionmentioning
confidence: 99%